2014
DOI: 10.4238/2014.february.28.10
|View full text |Cite
|
Sign up to set email alerts
|

Decreased risk of developing lung cancer in subjects carrying the CLPTM1L rs401681 (G>A) polymorphism: evidence from a meta-analysis

Abstract: ABSTRACT.A genome-wide association study revealed that a single nucleotide polymorphism, CLPTM1L -rs401681 (G>A), located at the 5p15.33 locus was significantly associated with increased risk of various cancers; however, its association with lung cancer is currently inconclusive. In order to explore the relationship between this polymorphism and lung cancer risk more precisely, we performed a meta-analysis of eight eligible studies involving 9935 cases and 11,261 controls. The pooled odds ratio (OR) and the 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Also associating with lung cancer risk was rs401681, a C/T intronic variant in CLPTM1L gene on chromosome 5p15.33; the T allele of rs401681 was previously found to associate with a lower risk of lung cancer in two meta-analyses 42 43 , and our results confirm these findings. On chromosome 8, we confirmed our previously observed association of the minor allele (G) of rs3019885 with increasing lung cancer risk 15 .…”
Section: Discussionsupporting
confidence: 89%
“…Also associating with lung cancer risk was rs401681, a C/T intronic variant in CLPTM1L gene on chromosome 5p15.33; the T allele of rs401681 was previously found to associate with a lower risk of lung cancer in two meta-analyses 42 43 , and our results confirm these findings. On chromosome 8, we confirmed our previously observed association of the minor allele (G) of rs3019885 with increasing lung cancer risk 15 .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, associations of these polymorphisms with lung carcinoma risk were observed both in current and former smokers. It is even compelling when considering the fact that the CLPTM1L -rs401681 (G > A) polymorphism was found to be significantly associated with decreased lung cancer risk, especially among European populations [25]. Also Tang et al [26] reported that the CLPTM1L gene rs402710 (C > T) and rs401681 (C > T) polymorphisms are associated with decreased cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…And meta-analysis is su cient to address these issues [47] . The results of previous meta-analysis con rmed the risk association between rs2736098, rs2736100, rs401681, rs402710, and rs31489 and LC, and analyzed the differences in LC susceptibility in different ethnic groups [48] [49][50] [51][52] [53][54] [55][56] [57][58] [59][60] [61] . However, most of these studies focused on single or several loci in the TERT-CLPTM1L region, and larger scale meta-analysis was still lacking.Tian J et al [62] recently conducted a large-scale meta-analysis and con rmed that eight sites in the TERT-CLPTM1L region (rs2853677, rs2242652, rs2736098, rs2736100, rs31489, rs401681, rs402710 and rs465498) were associated with LC risk, but they did not nd any other locus effects [2] .…”
Section: Introductionmentioning
confidence: 99%